Post-encoding administration of oxytocin selectively enhances memory consolidation of male faces in females - Wei Liu; Jiashen Li; Zhengyue Chen; Qingbai Zhao; Xiaojun Sun (Proceedings of the National Academy of Sciences, 2026)
Oxytocin plays a critical role in modulating social cognition and enhancing human memory for faces. However, it remains unclear which phase of memory oxytocin affects to enhance face memory. Our study explored oxytocin’s potential to selectively enhance the consolidation of social memories, specifically human faces, and whether this effect varies between genders. In three preregistered, randomized, double-blind, placebo-controlled trials with heterosexual participants (total N = 445, comprising 227 males and 218 females), we explored how oxytocin affects memory consolidation. We administered oxytocin immediately after encoding (i.e., Study 1), before retrieval (i.e., Study 2), and before encoding (i.e., Study 3) in three parallel studies. This design allowed us to confirm that oxytocin’s effects were indeed due to consolidation rather than retrieval or encoding. We found that administering oxytocin post-encoding, but not before-retrieval or before-encoding, significantly improved female participants’ ability to recognize male faces 24 h later, with no similar enhancement observed in males recognizing opposite-gender faces. Together with our analyses of the social placebo effect—where the belief in receiving oxytocin produces effects similar to those of actual intranasal oxytocin administration—and the approachability ratings during encoding, we concluded that oxytocin specifically enhances the consolidation of long-term social memories in women recognizing male faces. These findings imply that oxytocin selectively enhances the consolidation of human social memory, potentially deepening our understanding of the mechanisms underlying social memory processes.